Technological Integration for Biomechanical Monitoring and Ergonomic Prevention in Occupational Health. - Pereira Neto, Pedro; Thomazi, Gabriela; Oliveira, Vagner Muniz de (Journal of Health Sciences (2447-8938), 2025)
It is primarly essential to recognize that recent advances in health-focused technologies have produced solutions that extend well beyond traditional diagnostic and therapeutic care, enabling comprehensive assessment strategies and proactive preventive actions aimed at mitigating biomechanical risks in workplace environments. In this context, multisensory strategies gain particular relevance for developing wearable devices capable of continuously monitoring kinematic parameters and thereby contributing to the prevention of Repetitive Strain Injuries (RSI) and Work-Related Musculoskeletal Disorders (WMSDs). The present study describes the design and prototyping of an intelligent wrist orthosis integrating an MPU6050 inertial measurement sensor to capture and quantify kinetic and kinematic features of movement, an Arduino UNO microcontroller that processes and aggregates the collected signals, and an HC-05 Bluetooth module that transmits processed data and real-time feedback to mobile applications. The core objective of this work is to develop an Arduino-based intelligent orthosis for monitoring repetitive wrist movements, enhancing digital ergonomics, and integrating health and technology from a multidisciplinary perspective. The prototype was capable of identifying repetitive movements characteristic of typing with a sensitivity of 89.7% (95% CI: 86.2–92.4). Moreover, the broad capabilities of this technological approach underscore its utility for occupational health surveillance, enabling continuous evaluation of movement patterns, automated alerts for biomechanical deviations, and early identification of overload conditions that may precipitate musculoskeletal morbidity.